SMART SPECIALIZATION AS AN INSTRUMENT OF STRATEGIC DEVELOPMENT IN CHERNIHIV REGION - Македон, Г. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
Considering the European integration course of Ukraine, the processes of decentralization of power and the completion of the Strategy of Sustainable Development of Chernihiv Oblast for the period up to 2020, there is an urgent need to develop a new strategy that should include innovations for the development of an innovative economy and increase of investment attractiveness of the region. The article considers in detail the technique of smart-specialization, which is one of the fundamental principles of political and economic planning of the European Union, which is capable of combining the interests of all target groups in the region in an optimal way. The research is based on data from the Strategy of Smart Specializations of the European Union and the Smart Specialization Platform, taking into account the economic indicators of the Chernihiv region, using such methods as: dialectic, analysis and synthesis, economic-statistical method, graphical method, forecasting method, scientific abstraction, sample survey and grouping. The results of the study include a set of proposals for applying the principles of smart-specialization for the development of the Strategy for Sustainable Development of Chernihiv Oblast for the period up to 2027, which will ultimately lead to the economic growth of the region and its business structures and improve the well-being of the population. Application of the technique of smart-specialization to specific sectors of the regional economy of the region, such as tourism and information technology, will be subject to further research